A Study To Assess The Effectiveness Of Structured Teaching Programme On Self Care Management Among Patients With Uncontrolled Diabetes Mellitus (The Review of Diabetic Studies, 2024)
Rising rates of uncontrolled diabetes mellitus highlight the urgent need for effective patient education strategies that strengthen self-care practices and prevent complications. Structured teaching interventions have emerged as a practical approach for enhancing patient knowledge, particularly in settings where awareness levels remain low. The present investigation evaluated the effectiveness of a structured teaching programme on self-care management among adults with uncontrolled diabetes attending the Endocrinology Outpatient Department of NRI General Hospital, Chinakakani, Guntur District, Andhra Pradesh. Employing a pre-experimental onegroup pretest–posttest design, the study included 60 participants aged 31 years and above, selected through non-probability convenient sampling. Data were gathered using a structured questionnaire that assessed sociodemographic characteristics, general diabetes-related information, and knowledge across 45 self-care items. Following the pretest, participants received a structured teaching programme that addressed diet, physical activity, medication adherence, healthcare follow-up, lifestyle modifications, and management of complications through visual and interactive teaching aids. A posttest administered after 15 days demonstrated a substantial improvement in knowledge, with adequate knowledge increasing from 0% in the pretest to 61.6% in the posttest. Mean knowledge scores rose from 18.8±11.45 to 37.8±7.24, and the paired t-test (t=3.465, p